12x-5x-3=0

Simple and best practice solution for 12x-5x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-5x-3=0 equation:


Simplifying
12x + -5x + -3 = 0

Reorder the terms:
-3 + 12x + -5x = 0

Combine like terms: 12x + -5x = 7x
-3 + 7x = 0

Solving
-3 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 7x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 7x = 0 + 3
7x = 0 + 3

Combine like terms: 0 + 3 = 3
7x = 3

Divide each side by '7'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| 6x-5=9+2 | | 40+4y=y^2+4 | | X+20=9(x-4) | | (12-4i)(3+i)=0 | | c(ad)+x=bd+ad(yz) | | 5x^2=9x-5 | | 360-2x=100 | | 22n=100 | | -10y-3=7y | | (2abc)(-3abc)(-5a)= | | Y=30x+.10 | | -6v+2=1 | | xsquared-7x=-3 | | -6v+2=11 | | 49=2y+17 | | 5(2-4)=30 | | (2abc)(-3abc)(-5)= | | 2x(x+3)-3(2x-3)= | | x^3+-10x+25=0 | | (4v+1)(3+v)=0 | | x^3-10x+26=0 | | 2(x+1)=4x+2 | | 2y-24x=10 | | -2x^2-2x-12=0 | | -2=3y+7 | | -2x-9y=1 | | 36y=1 | | 28+24p=36p | | 2x^3-6x^2-x=0 | | a^3b^2(3a^2b)= | | 6-(3x-6)=7x-9 | | log(7)1= |

Equations solver categories